The Analysis of Figurative Language in “The Sky is Low, The Clouds Are Mean”, “We Outgrow Love Like Other Things”, And “Hope Is The Thing With Feathers” By Emily Dickinson - Batrisya Amalia Putri; Tuti Handayani (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study explores the use of figurative language in selected poems by Emily Dickinson, with a focus on how metaphor, simile, personification, symbol and hyperbole enhance the literary experience. The research aims to identify, categorise, and analyse the various types of figurative language used in Dickinson's poetry. Using a descriptive-qualitative method, the study reveals that Dickinson's poems employ a wide range of figurative language techniques to express complex emotions and themes, reflecting the intricate relationship between human experience and literary expression. There are 16 figurative languages in these three selected poems by Emily Dickinson; there are 5 personifications, 2 hyperboles, 2 similes, 4 symbols, and 3 metaphors. The findings suggest that figurative language not only enriches the text but also deepens the reader's understanding of the poet's intended messages.